The Use Of Physical Restraint: An Argumentative Essay - Abdeljawad, Rami; Mrayyan, Majd T. (European Scientific Journal, ESJ, 2016)
This study was conducted to review the literature about the use of physical restraints as an argumentative issue. The use of physical restraints has been reported with varying prevalence from 41% to 64% according to epidemiological studies. In this study, the author reviewed the opinions of the opponent and proponent viewpoints regarding physical restraints from legal and ethical perspectives. The ideas of proponents implied that the use of physical restraints offers protection for patients and others as well as ensures introducing good treatment. On the other hand, the opponents think that the use of physical restraints is not well safe and associated with legal and ethical issues. Furthermore, psychological injuries and mental problems have been reported to be associated with the use of physical restraints. The author agrees with the opponents and does not support the use of physical restraints because it involves ethical, legal and health impacts.